Entrepreneurial intentions of Gen Z university students and entrepreneurial constraints in Bangladesh - Mohammad Imtiaz Hossain; Mosab I. Tabash; May Ling Siow; Ong Tze San; Suhaib Anagreh (Journal of Innovation and Entrepreneurship, 2023)
This research examines a variety of restrictions preventing Bangladeshi youth, particularly Generation Z university students, from becoming involved in entrepreneurship. Moreover, the study examines the influence of Entrepreneurial Attitude (EA), Subjective Entrepreneurial Norms (SEN), Entrepreneurial Perceived Behavioural Control (EPBC), and Entrepreneurial Resilience (ER) on Entrepreneurial Intention (EI) of Bangladeshi Gen Z university students. A systematic literature review methodology following PRISMA procedure was performed to identify the relevant articles. A quantitative method with a positivism philosophy, cross-sectional time horizon and deductive approach was applied to the study. The data of 206 university students from the BBA department of ten universities were collected using convenience sampling and a self-administrated structured questionnaire survey. SPSS 26.0 and Smart PLS 3.0 were used to analyse the data. The output shows a positive and significant association amongst EA, SEN, EPBC, ER, and EI. Various constraints were identified from the literature and ranked based on the respondents' feedback. This research will help entrepreneurs, scholars, policymakers and practitioners to build the entrepreneurial ecosystem and develop young people's understanding of the entrepreneurial decision process and the importance of ER. This paper contributes through empirical investigation to an understanding of the actions that prevent Gen Z students from entrepreneurial activities; decisions are affected by socio-psychological constructions integrating ER with the Theory of Planned behaviour (TPB) model. Triple, Quadruple and Quintuple Helix models are considered supporting theories in this study to shed light on tackling the constraints. To the best knowledge of the researcher, integrating ER with TPB model's constructs is a pioneer scholarly contribution in the context of South-East Asian, specifically Bangladeshi Gen Z students.
Keywords: 650; Attitude; Behavioural control; Constraints; Entrepreneurship; Gen Z; Resilience; Subjective norms